1994
DOI: 10.1139/v94-126
|View full text |Cite
|
Sign up to set email alerts
|

Near ultraviolet photolysis of phosphine studied by H atom photofragment translational spectroscopy

Abstract: . Can. J. Chem. 72,977 (1 994).We report time-of-flight measurements of the H atom fragments arising in the photodissociation of phosphine at three near ultraviolet excitation wavele_ngths -2 18.2 nm, 221.6 nm, and 228.0 nm. For these wavelengths, energetic considerations dictate that ground state PH2(X) fragments must be the partner product of the primary photolysis event. The measured H atom kinetic energy distributions indicate that internal excitation of these partner fragments accounts for the major part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…The distribution shown in Figure 6 indicates that reaction 3 dominates, with high AsH 2 (X ˜) rovibrational excitation. This is reasonable in light of the photodissociation dynamics of PH 3 [21][22][23] and NH 3 . 12-14,17 Ultraviolet photoexcitation results in a change of equilibrium geometry.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The distribution shown in Figure 6 indicates that reaction 3 dominates, with high AsH 2 (X ˜) rovibrational excitation. This is reasonable in light of the photodissociation dynamics of PH 3 [21][22][23] and NH 3 . 12-14,17 Ultraviolet photoexcitation results in a change of equilibrium geometry.…”
Section: Discussionsupporting
confidence: 75%
“…For example, Lambert et al observed PH 2 with substantial bending excitation and a-axis rotation following the ultraviolet photolysis of PH 3 . 21 In contrast, it is known that NH 2 is formed with a relatively modest amount of bending excitation. [12][13][14]17 The equilibrium bond angles for AsH 3 (A ˜) and AsH 2 (X ˜) are 112°(an estimate based on AsH 3 + and PH 3 (A ˜)) and 90.4°, 39 respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…79 The A ˜state of PH 3 has a non-planar equilibrium geometry but, as in ammonia, the A ˜and X ˜state PESs exhibit a CI at planar configurations and extended R H-PH 2 , 79 thereby allowing efficient dissociation to ground state H + PH 2 (X ˜) products. 17,80 The limited available data relating to AsH 3 photochemistry (at 193.3 nm) suggests that this molecule also exhibits broadly similar dissociation dynamics. 81 Many of the parallels between H 2 O and CH 3 OH are evident also when comparing NH 3 and CH 3 NH 2 .…”
Section: Ammonia Alkyl Amines and Cyclic Aminesmentioning
confidence: 99%